2010
DOI: 10.1073/pnas.1009700107
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase-4 mediates protection against chronic load-induced stress in mouse hearts by enhancing angiogenesis

Abstract: Cardiac failure occurs when the heart fails to adapt to chronic stresses. Reactive oxygen species (ROS)-dependent signaling is implicated in cardiac stress responses, but the role of different ROS sources remains unclear. Here we report that NADPH oxidase-4 (Nox4) facilitates cardiac adaptation to chronic stress. Unlike other Nox proteins, Nox4 activity is regulated mainly by its expression level, which increases in cardiomyocytes under stresses such as pressure overload or hypoxia. To investigate the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
438
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 407 publications
(472 citation statements)
references
References 41 publications
25
438
8
1
Order By: Relevance
“…Our observations are also consistent with recent observations that Nox4 KO mice are deficient in their angiogenic response to the same hind-limb ischaemia implemented to RIa redox-dead mice [9][10][11] . Discussion Nox-derived oxidants can act as powerful mediators of growth factor signalling 10,11,20 . However, the targets of these oxidants and the mechanism by which they enhance vessel growth have remained elusive.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are also consistent with recent observations that Nox4 KO mice are deficient in their angiogenic response to the same hind-limb ischaemia implemented to RIa redox-dead mice [9][10][11] . Discussion Nox-derived oxidants can act as powerful mediators of growth factor signalling 10,11,20 . However, the targets of these oxidants and the mechanism by which they enhance vessel growth have remained elusive.…”
Section: Resultssupporting
confidence: 93%
“…Recently three independent studies have specifically implicated Nox4 as an isozyme of NADPH oxidase that coupled to angiogenesis [9][10][11] . Consequently, we compared VEGF-induced RIa oxidation in the aorta from Nox4 knockout (KO) mice with littermate WTs, finding the former were substantially deficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nox4-derivd ROS has also been suggested in cellular senescence and aging (104) and in insulin-mediated differentiation of adipocytes (177). Recent studies demonstrated that Nox4 may actually have protective effects, possibly through Nox4-derived H 2 O 2 , which may act as a vasodilator in some vascular beds (164,238). This could explain why mice with targeted endothelial Nox4 overexpression have lower blood pressure and improved endothelium-dependent vasodilation versus wild-type controls (164).…”
Section: Nox4mentioning
confidence: 94%
“…In fact, in some conditions, even the same approach yields divergent results. Mice in which Nox4 was targeted in a cardiac-specific manner demonstrated that Nox4 is both protective 21 and injurious 22 in models of cardiac overload.…”
Section: Article See P 1217mentioning
confidence: 99%